2002
DOI: 10.1148/radiol.2241010654
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Artery Embolization for Hemoptysis in Young Patients with Cystic Fibrosis

Abstract: BAE had a high success rate for short-term control of bleeding; however, more than half the patients required repeat embolization during the long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 31 publications
2
44
0
8
Order By: Relevance
“…Life threatening massive haemoptysis is successfully treated in the short term with bronchial artery embolisation [8,9]. However, 55% of patients with cystic fibrosis required more than one embolisation procedure to achieve long-term control of their haemoptysis [8].…”
Section: Discussionmentioning
confidence: 99%
“…Life threatening massive haemoptysis is successfully treated in the short term with bronchial artery embolisation [8,9]. However, 55% of patients with cystic fibrosis required more than one embolisation procedure to achieve long-term control of their haemoptysis [8].…”
Section: Discussionmentioning
confidence: 99%
“…From a practical standpoint, the noninvasive approach provided by CTA is expected to modify the recommendations for the angiographic procedures according to which thoracic aortography should be performed before [23] or after [24] bronchial artery embolization to identify all the systemic arterial supply to the bleeding site. Owing to the possibility to detect not only ectopic bronchial arteries, but also abnormal nonbronchial systemic arteries [10,25], CTA should contribute to the improvement of the immediate success rate of embolization whatever the underlying disease [26][27][28][29][30][31][32]. In three patients of our study group, the instable Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Immediate control of hemoptysis with BAE has been reported in 57–100% of patients [12,26,44,113,114,115,116,117,118,119,120,121]. This wide range of success rates across studies can be partially attributed to heterogeneity with regard to analysis of results [122].…”
Section: Management Of Massive Hemoptysismentioning
confidence: 99%
“…Barben et al [121] reported the need of a second embolization in 55% (11/20) of their cystic fibrosis patients, with a median time interval of 4 months between the first and second procedures. Recurrence of hemoptysis may be due to incomplete embolization of the bronchial vessels, recannalization of the embolized arteries, presence of nonbronchial systemic arteries, or development of collateral circulation in response to continuing pulmonary inflammation [12,114,115,123].…”
Section: Management Of Massive Hemoptysismentioning
confidence: 99%